STRESS LOAD AND STRESS RESILIENCES ON CARDIORESPIRATORY ENDURANCE (VO2MAX) IN ELDERLY GROUP - Setiawan Setiawan; Yuni Susanti Pratiwi; Elvine Gunawan; Ambrosius Purba (JURNAL ILMU FAAL OLAHRAGA INDONESIA, 2022)
Stress both psychologists and nonpsychological always found in everyday life. Stressors obtained in every activity of our daily activities both in low to severe stresses. Good stress adaptation can also affect a person in coping with the stress he experiences in adaptive coping person. Stress is also feared can adversely affect the physiological conditions. In this study conducted a regression analysis between stress load and stress resistance to VO2max of elderly group. The participants recruited by 116 professors, in elderly group. We included individuals with clinical evidence as based upon medical interview, physical examination, and physical fitness test. On statistical result of multiple regression analysis data showed very low correlation interpretation based on correlation stress load and stress resilience on cardiorespiratory endurance (VO2max). Its mean the data also showed that 0,8% contribution of dependent variable (VO2max) and independent variable affect (Stress Load and Stress Resilience). On the result study showed no significant effect on Stress Load and Stress Resilience on cardiorespiratory endurance (VO2max) in elderly group. The result of partial regression coefficient test shows that is no significant effect between stress load and cardiorespiratory endurance (VO2max) of the elderly group (t = -1.112< t table =1.975). The stress resilience variable partially is no significant effect between stress load and cardiorespiratory endurance (VO2max) of the elderly group (t=-0.115 < t table =1.975). Based on our study, it can be concluded that stress load and stress resilience have not affected the cardiorespiratory endurance (VO2max) of the elderly group of Padjadjaran University Professors.